Simulation Investigation of SPWM, THIPWM and SVPWM Techniques for Three Phase Voltage Source Inverter - Zulkifilie Bin Ibrahim; Md. Liton Hossain; Ismadi Bin Bugis; Nik Munaji Nik Mahadi; Ahmad Shukri Abu Hasim (Institute of Advanced Engineering and Science, 2014)
Pulse width modulation (PWM) technique is one of the vital issues for power electronic circuit control. A number of Pulse width modulation (PWM) techniques are increasingly applied in many new industrial applications that require superior performance. The most widely applied PWM technique for three-phase voltage source inverters are Sine Pulse Width Modulation (SPWM), Third Harmonic Injection Pulse Width Modulation (THIPWM) and Space Vector Pulse Width Modulation (SVPWM). SPWM is the most simple modulation technique that can realize easily in analog circuit. However, it has some drawbacks such as higher total harmonic distortion (THD), lower switching frequency and not capable in over modulation region. THIPWM and SVPWM both provide better THD compared to SPWM. SVPWM shows lower THD in over modulation region and in high frequency application compared to THIPWM. These three techniques are discussed, analyzed and compared in terms of modulation index, switching frequency and inverter input voltage in this paper. The modeling and simulation for all PWM techniques have been done by using MATLAB/SIMULINK and Origin 6.1. From the simulation results, SVPWM shows the best performance and meet IEEE 519 standard of current harmonics level.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5833